A Matrix Iteration for Finding Drazin Inverse with Ninth-Order Convergence - A. S. Al-Fhaid; S. Shateyi; M. Zaka Ullah; F. Soleymani (Abstract and Applied Analysis)
The aim of this paper is twofold. First, a matrix iteration for finding approximate inverses of nonsingular square matrices is constructed. Second, how the new method could be applied for computing the Drazin inverse is discussed. It is theoretically proven that the contributed method possesses the convergence rate nine. Numerical studies are brought forward to support the analytical parts.